Importin-β From the Recretohalophyte Limonium bicolor Enhances Salt Tolerance in Arabidopsis thaliana by Reducing Root Hair Development and Abscisic Acid Sensitivity - Xu, Yanyu; Jiao, Xiangmei; Wang, Xi; Zhang, Haonan; Wang, Baoshan; Yuan, Fang (Frontiers in Plant Science, 2021)
Aims: To elucidate the genetics underlying of salt tolerance in recretohalophytes and assess its relevance to non-halophytes, we cloned the Limonium bicolor homolog of Arabidopsis thaliana (Arabidopsis) SUPER SENSITIVE TO ABA AND DROUGHT2 (AtSAD2) and named LbSAD2, an importin-β gene associated with trichome initiation and reduced abscisic acid (ABA) sensitivity, and heterologously expressed LbSAD2 in Arabidopsis. Methods: We examined LbSAD2 expression and assessed the effect of heterologous LbSAD2 expression in Arabidopsis on root hair/trichome induction and the expression levels of possible related genes in trichome/root hair development, some physiological parameters involved in salt tolerance including germination rate, root length, contents of Na+ proline and malondialdehyde, and the response of ABA at germination stage. Results: LbSAD2 gene is highly expressed in salt gland development stage and salt treatment, specially located in salt gland by in situ hybridization, and LbSAD2 protein contains some special domains compared with AtSAD2, which may suggest the involvement of LbSAD2 in salt tolerance. Compared with SAD2/GL1 mutants CS65878, which lack trichomes, CS65878-35S::LbSAD2 had higher trichome abundance, but lower root hair abundance. Under 100 mM NaCl treatment, CS65878-35S::LbSAD2 showed enhanced germination and root lengths; improved physiological parameters, including high proline and low contents of Na+ and malondialdehyde; higher expression of the salt-tolerance genes Δ1-PYRROLINE-5-CARBOXYLATE SYNTHETASE 1 (P5CS1) and GST CLASS TAU 5 (GSTU5); reduced ABA sensitivity; and increased expression of the ABA signaling genes RESPONSIVE TO ABA 18 (RAB18) and SNF1-RELATED PROTEIN KINASE 2 (SRK2E), but not of the ABA biosynthesis gene 9-CIS-EPOXYCAROTENOID DIOXYGENASE 3 (NCED3). Conclusions: LbSAD2 enhances salt tolerance in Arabidopsis by specific reducing root hair development, Na+ accumulation, and ABA sensitivity.